2019
DOI: 10.1080/17469899.2019.1635456
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in patients with ocular hypertension or glaucoma

Abstract: Introduction: Nonadherence to medication is a challenge to effective treatment of many chronic diseases, including glaucoma, and persists even with interventions aimed at improving adherence. The reported rates of nonadherence to topical glaucoma medication vary widely from 16% to 67%, and it is estimated that less than a third of patients remained on their initial therapy after 12 months. Nonadherence can lead to disease progression and increased economic burden. Areas covered: This review examines factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 88 publications
1
38
0
Order By: Relevance
“…Moreover, other common risk factors were previously identified [ 12 14 ]. All of these risk factors need to be solved by education, communication with patients, and patient training in improving proficiency of self-administration of eye drops [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other common risk factors were previously identified [ 12 14 ]. All of these risk factors need to be solved by education, communication with patients, and patient training in improving proficiency of self-administration of eye drops [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for nonadherence to glaucoma therapies include patients’ problems (financial concern, poor understanding of the disease, and frequent eye drop application), healthcare providers’ issues (insufficient instruction/explanation and assessment of each patient’s conditions), and the relationship between patients and physicians (lack of communication and trust) [ 12 14 ]. A previous study reported that a fixed-combination therapy improved the long-term adherence of patients with glaucoma compared with the unfixed therapy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other common risk factors were previously identi ed. [12][13][14] All of these risk factors need to be solved by education, communication with patients, and patient training in improving pro ciency of self-administration of eye drops. 42 Speci c reasons on why physicians prescribed un xed combinations for certain patients would be interesting to identify.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Risk factors for nonadherence to glaucoma therapies include patients' problems ( nancial concern, poor understanding of the disease, and frequent eye drop application), healthcare providers' issues (insu cient instruction/explanation and assessment of each patient's conditions), and the relationship between patients and physicians (lack of communication and trust). [12][13][14] A previous study reported that a xed-combination therapy improved the long-term adherence of patients with glaucoma compared with the un xed therapy. 15 According to a nationwide survey performed in 2011-2012 in Japan using a questionnaire, good adherence to IOP-lowering eye drops was observed in 72.4% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Risk factors for nonadherence to glaucoma therapies include patients' problems ( nancial concern, poor understanding of the disease, and frequent eye drop application), healthcare providers' issues (insu cient instruction/explanation and assessment of each patient's conditions), and the relationship between patients and physicians (lack of communication and trust). [12][13][14] A previous study reported that a…”
Section: Introductionmentioning
confidence: 99%